FORMULATION DEVELOPMENT AND EVALUATION OF ELEMENTARY OSMOTIC TABLET OF LISINOPRIL DIHYDRATE - BHAIRAV, BHUSHAN A.; KHANDAGALE, PRADNYA M.; SAUDAGAR, R. B. (International Journal of Current Pharmaceutical Research, 2017)
Objective: Lisinopril Dihydrate is one of the antihypertensive drug used to control the high blood pressure. Osmotically Controlled release tablet of Lisinopril Dihydrate was performed for reducing dosing frequency and patient compliance. Methods: Elementary osmotic tablets of Lisinopril Dihydrate were developed using Sodium chloride as a key ingredient which gives osmogent property which provides driving force inside the core tablet and which leads to release of the drug. Microcrystalline cellulose used as a release retardant material in the present work. Different formulations were prepared by varying the concentrations using 32 factorial designs. It was applied to see the effect of variables Sodium chloride (X1) and MCC (X2) on the response percentage drug release as a dependent variable. These formulations were evaluated for, Hardness, Flow property, Thickness, Friability, Drug content and In vitro drug release. Tablets were coated with a semipermeable membrane using 5% w/v cellulose acetate(CA) in acetone and PEG 400(1%) used as Plasticizer. Coated Elementary osmotic tablets were drilled for delivery orifice using a standard micro drill of diameter size 0.8 mm. Results: Drug release rate was increased as the increase in the concentration of sodium chloride and release rate decreased on increasing the concentration of MCC. Drug release rate was directly proportional to delivery orifice size. SEM Study carried out for detection of diameter size of the delivery orifice. The FTIR studies demonstrate that there was no interaction between polymer and drug. Conclusion: The optimized formulation was stable for 3 mo of accelerated stability study